1975
DOI: 10.1002/1097-0142(197501)35:1<129::aid-cncr2820350118>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface immunoglobulin positive lymphocytes in human breast cancer tissue and homolateral axillary lymph nodes

Abstract: Surface immunoglobulins were determined on human lymph node lymphocytes by the use of immunofluorescence technique in 59 breast cancer patients undergoing radical mastectomy. In 10 of these cases, lymphocyte surface immunoglobulins were also studied on lymphocytes infiltrating the primary cancer mass. The most outstanding finding was a difference between the IgM lymphocyte populations in the lymph nodes of patients with and without lymph node metastases. When cancer tissue was present in one or more lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 6 publications
0
12
1
Order By: Relevance
“…This disagrees with Burtin et al (1969) who found IgA to be predominant in tumourdraining nodes. Again, tumour spread to the axilla did not increase the percentage of the IgM-bearing lymphocyte subpopulations in our study, and contrasts with the findings of Richters & Kaspersky (1975). There was, however, a reversal of the IgA:IgD ratio in tumour-free axillary lymph nodes where axillary spread of tumour had occurred.…”
Section: Tumour Histologycontrasting
confidence: 99%
See 1 more Smart Citation
“…This disagrees with Burtin et al (1969) who found IgA to be predominant in tumourdraining nodes. Again, tumour spread to the axilla did not increase the percentage of the IgM-bearing lymphocyte subpopulations in our study, and contrasts with the findings of Richters & Kaspersky (1975). There was, however, a reversal of the IgA:IgD ratio in tumour-free axillary lymph nodes where axillary spread of tumour had occurred.…”
Section: Tumour Histologycontrasting
confidence: 99%
“…Black et al, 1953;Wartman, 1959;Hamlin, 1968;Silverberg et al, 1970). Recently, alterations of lymphocyte subsets have also been described in tumour-draining lymph nodes (Richters & Kaspersky, 1975;Tsakraklides et al, 1975a;Eremin et al, 1976;Saxon & Portis, 1977).…”
mentioning
confidence: 98%
“…The tumor microenvironment (TME) is the soil to develop tumors, and has an extremely important role in the tumorigenesis, development and prognosis of cancers [47,48]. The disorder of the liver environment could cause various problems, such as abnormal angiogenesis, destruction of extracellular matrix (ECM), and severe inflammation [49][50][51][52][53]. Therefore, the disorder of the TME might be one of the key factors for carcinogenesis and progression of the primary HCC with multiple lesions.…”
Section: Discussionmentioning
confidence: 99%
“…evaluating NG twice in the same patients at different tines obtained a coincidence of over 90 percent of the cases. According to Cutler et al (1966) Tsakraklides (1974) and his associates claimed that the patients whose lymph nodes showed a predominance of lympho cytes and germinal centers had a favorable prognosis; in these the host defensive immune response was playing a significant role (Sherwin and Richters 1972;Richters and Kaspersky 1975). Their classification seems to be reasonable from a newly established immunological point of view .…”
Section: Sh and Prognosismentioning
confidence: 99%